Analisis Keuntungan Usaha Penangkaran Burung Murai Batu (Copsychus malabaricus) Di Kota Bengkulu - Heri Dwi Putranto; Yossie Yumiati; Alven Syahril Muslim; Ahmad Saleh Harahap (Wahana Peternakan, 2022)
Abstract Nowadays, breeding captivity of white-rumped shama (Copsychus malabaricus) becomes a popular business among bird lovers in Bengkulu. It has been directed to create an independent livestock business. This captivity business aims to increase household income and gain profits. Captivity breeding has developed into a promising and potential business. This study aimed to analyze the profits of white-rumped shama breeding captivity business in Bengkulu city. The research was purposively conducted in Bengkulu City. A snowball sampling method was used to determine respondents. Total of 19 respondents were interviewed based on questionairres to determine the characteristics of respondents, total cost, total revenue and R/C ratio. The results showed that the majority of white-rumped shama breeders in Bengkulu city were male (95%) and classified into a productive age group. The average total revenue was Rp 150,744,354/year per respondent. The average of R/C ratio was 2.47, which means that white-rumped shama breeding captivity business in Bengkulu is feasible to be developed. Key words: Bengkulu City, Breeding Captivity, Profit Analyses, White-rumped Shama